2020
DOI: 10.1177/0145561320901613
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of High-Risk Factors for Cervical Lymph Node Metastasis in Laryngeal Squamous Cell Carcinoma and Establishment of Nomogram Prediction Model

Abstract: Laryngeal squamous cell carcinoma (LSCC) is one of the most common laryngeal tumors, and its incidence is increasing yearly; however, whether lymph node dissection should be performed during surgery remains unclear. We retrospectively analyzed the clinical and pathological data of 246 cases of LSCC and developed a nomogram for the prediction of lymph node metastasis (LNM) of LSCC. The predictive performance and consistency of the model were evaluated using the consistency coefficient (C-index) and calibration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
(21 reference statements)
1
11
1
Order By: Relevance
“…In addition, we also found that age at diagnosis, race, primary site, number of tumours, tumour size, grade, and T-stage were closely associated with the occurrence of LNM of LC by univariate and multivariate logistic regression analyses (Tables 2 and 3 ). Among them, T-stage, grade, and tumour size have been previously reported as independent risk factors for LNM in LC patients, which is consistent with our study findings, indicating that these variables play an important role in promoting LNM in LC patients [ 34 ]. Our multivariate logistic regression analysis further demonstrated that the primary site was a risk factor for LNM ( Table 3 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, we also found that age at diagnosis, race, primary site, number of tumours, tumour size, grade, and T-stage were closely associated with the occurrence of LNM of LC by univariate and multivariate logistic regression analyses (Tables 2 and 3 ). Among them, T-stage, grade, and tumour size have been previously reported as independent risk factors for LNM in LC patients, which is consistent with our study findings, indicating that these variables play an important role in promoting LNM in LC patients [ 34 ]. Our multivariate logistic regression analysis further demonstrated that the primary site was a risk factor for LNM ( Table 3 ).…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, various risk factors for LNM of LC have been reported, and prediction models have been established [ 8 , 34 ]. However, due to the complexity and large size of the various factors in the data and the differences among the calculation methods of the models, the prediction performance was also significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with most studies, supraglottic cancer was a risk factor for lymph node metastasis, 15,19,20 whose relative risk of lymph node metastasis was close to 3 times that of glottic cancer. For poorly differentiated laryngeal cancer, the possibility of lymph node metastasis was significantly higher than that of welldifferentiated cancer, 14,20 and the relative risk of lymph node metastasis was twice that of well-differentiated laryngeal cancer. In addition, we also found a two-fold increase in lymph node metastasis in patients with tumor size >5cm compared with those with tumor size <3cm.…”
Section: Discussionmentioning
confidence: 93%
“…For patients with laryngeal cancer, the more advanced the T classification gets, the greater possibility of lymph node metastasis there is. [12][13][14][15] Positive cervical lymph nodes have a negative impact on the patient's prognosis, and LND for such patients can improve survival significantly. 16 Similarly, our study also showed that the survival of elderly patients with laryngeal cancer (including OS and CSS) with lymph node metastasis was significantly inferior to that of patients without metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…However, we detected no occult LNM in any T1 cases or any well-differentiated LSCCs. In the study by Chen et al 12 regarding high risk factors for cervical LNM in LSCC, they found a significant relationship between T stage, tumor grade, and LNM. In our study, parallel to the literature, we found a significant relationship between T stage ( p = 0.017), tumor grade ( p = 0.005), and occult LNM; there was no LNM in T1 or well-differentiated cases.…”
Section: Discussionmentioning
confidence: 94%